ASSOCIATION BETWEEN CRITICAL, CREATIVE THINKING AND PROBLEM SOLVING IN ACCOUNTING RESEARCHES: AN OVERVIEW - Nimalathasan, B. (My University, 2010)
The paper is attempted to focus on association between critical, creative thinking and problem solving in accounting researches. The professional accountant must possess thinking skills (i.e., inquisitiveness; open-mindedness; patience, thoroughness, and perseverance) to operate in an increasingly complex environment. These skills assist accountants in problem solving and decision making in general, and in professional research activities in particular. The present study is based on the secondary data. The collected data may be processed and analyzed in order to make the present study useful to the readers, interested parties and policy makers of the concern area. Further, the present study also tries to contribute to this literature by doing the research.
Keywords: critical; creative thinking; problem solving; accounting researches